FILSAFAT ILMU BIMBINGAN DAN KONSELING ISLAM: INTEGRASI ASPEK ILMIAH DAN ILAHIAH - Mohamad Thohir (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2021)
This study aims to present a more complete understanding of science philosophy of Islamic Guidance and Counseling by examining it from a philosophical point of view so that it deserves to be called an independent science. Islamic guidance and counseling as an independent science will be able to know what the object of study is, it can be verified, can be traced to the source and method of obtaining it, as well as visible ethics, aesthetics and benefits. This study seeks to find out the paradigm of science of BKI in Islamic Religious Higher Education (PTKI), more precisely the BKI Study Program which is under the auspices of the Da'wah Faculty at UIN, IAIN and STAIN and to see its position beside the BK Study Program at non-PTKI universities. This paper is the result of library research which explores data on the science of BKI from various sources, ranging from books, articles, journals and online media. The results of the study show that there are different paradigms in viewing the science of guidance and counseling between western scientists and Islam, where the truth of science in the west is determined by ratio and senses, while Islam rests its truth on revelation (Al-Qur'an and Hadith), which is also does not leave the findings of the ratio and senses.